2021
DOI: 10.1038/s41525-021-00195-8
|View full text |Cite
|
Sign up to set email alerts
|

Genes and pathways monotonically dysregulated during progression from normal through leukoplakia to gingivo-buccal oral cancer

Abstract: Oral squamous cell carcinoma of the gingivo-buccal region (OSCC-GB) accounts for the highest cancer morbidity and mortality among men in India. It has been observed that about one-third of individuals with oral leukoplakia, a dysplastic precancerous lesion in the oral cavity, progress to oral cancer. We aimed to identify systematic transcriptomic changes as a normal tissue in the oral cavity progresses to frank OSCC-GB. Seventy-two OSCC-GB patients, from multiple hospitals, were recruited, and transcriptome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
(68 reference statements)
1
19
0
Order By: Relevance
“…In the oral cavity, leukoplakia (oral leukoplakia or OLK) is a white thickening of the mucosa, which progresses to overt cancer in 9% of individuals and our understanding of this process has, until recently, been limited [1]. Previous studies have identified immunological dysregulation, increasing mutation burden as well as specific changes to signaling pathways and epidermal growth factor receptor (EGFR) amplification with similarity as well as differences compared with squamous cell carcinoma (SCC), the predominant cancer of the oral cavity [2][3][4].…”
mentioning
confidence: 99%
“…In the oral cavity, leukoplakia (oral leukoplakia or OLK) is a white thickening of the mucosa, which progresses to overt cancer in 9% of individuals and our understanding of this process has, until recently, been limited [1]. Previous studies have identified immunological dysregulation, increasing mutation burden as well as specific changes to signaling pathways and epidermal growth factor receptor (EGFR) amplification with similarity as well as differences compared with squamous cell carcinoma (SCC), the predominant cancer of the oral cavity [2][3][4].…”
mentioning
confidence: 99%
“…As high intracellular ROS levels can induce cell damage and even death, we speculate this may change the relative markers. To date, some biological biomarkers have been reported of potential value in predicting malignant transformation of oral leukoplakia, such as ALDH1, p53, Cyclin D1, PDCD5, and PDPN [ 43 45 ]. ALDH1, an isomer of aldehyde dehydrogenase, has been demonstrated to be a tumor stem cell marker for various solid tumors, including OSCC, and can be used as a prognostic marker for head and neck squamous cell carcinoma (HNSCC) survival [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pathways that were upregulated among case samples in analysis 2 that are not confounded by later results included connections to primary immunodeficiency (ko05340) and RNA degradation (ko03018), both of which have been researched in the cancer literature. Primary immunodeficiency has been found significantly enriched among gingivo-buccal oral cancer samples (Das et al, 2021 ). Moreover, Goodall and Wickramasinghe ( 2021 ) summarized mounting evidence on the alteration of RNAs as it contributes to cancer in a recent review.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 99%